2020
DOI: 10.1093/eurheartj/ehz917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clopidogrel vs. prasugrel vs. ticagrelor on endothelial function, inflammatory parameters, and platelet function in patients with acute coronary syndrome undergoing coronary artery stenting: a randomized, blinded, parallel study

Abstract: Aims In a randomized, parallel, blinded study, we investigate the impact of clopidogrel, prasugrel, or ticagrelor on peripheral endothelial function in patients undergoing stenting for an acute coronary syndrome. Methods and results The primary endpoint of the study was the change in endothelium-dependent flow-mediated dilation (FMD) following stenting. A total of 90 patients (age 62 ± 9 years, 81 males, 22 diabetics, 49 non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 52 publications
2
46
0
5
Order By: Relevance
“…Platelets have been recognized as crucial regulators of inflammatory processes under various pathophysiological conditions ( Karhausen et al, 2020 ). The inflammation caused by overactivated platelets can further promote the development of thrombosis, atherosclerosis, and cardiovascular diseases ( Barrett et al, 2019 ; Garshick et al, 2020 ; Schnorbus et al, 2020 ). Platelets exert critical roles in the development of inflammatory diseases such as inflammatory bowel disease (IBD) ( Chimen et al, 2019 ; Petrey et al, 2019 ; Nicolai and Massberg, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Platelets have been recognized as crucial regulators of inflammatory processes under various pathophysiological conditions ( Karhausen et al, 2020 ). The inflammation caused by overactivated platelets can further promote the development of thrombosis, atherosclerosis, and cardiovascular diseases ( Barrett et al, 2019 ; Garshick et al, 2020 ; Schnorbus et al, 2020 ). Platelets exert critical roles in the development of inflammatory diseases such as inflammatory bowel disease (IBD) ( Chimen et al, 2019 ; Petrey et al, 2019 ; Nicolai and Massberg, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic patients presented with non-ST-segment elevation ACS [ 31 ], ticagrelor showed better improvement of endothelial function (indicated by FMD) compared to prasugrel, which has been explained by an increased adenosine level. However, other studies reported that ticagrelor did not improve endothelial function compared to prasugrel and clopidogrel [ 32 ]; rather, endothelial function was improved during prasugrel treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, another study recently reported prasugrel to better prevent the endothelial dysfunction and inflammation associated with coronary stenting and NSTEMI, as compared with clopidogrel or ticagrelor. 63 Following these results, the 2020 ESC guidelines have granted a class IIb evidence favoring prasugrel over ticagrelor in patients with NSTEMI undergoing PCI, and for whom use of potent P2Y12 inhibitors is indicated. The loading dose of P2Y12 inhibitors may be administered as soon as the coronary angiogram is performed and prior to PCI.…”
Section: Which P2y 12 Inhibitors In the Acute Setting?mentioning
confidence: 99%